Penerapan Teknologi Lubang Resapan Biopori di Desa Dahu - Salma Naba Johari; M.Roby Iskandar; Mohamad Ikrom Rasid; Supriyadi Supriyadi; Syifa Silfiyana; Ilham Arifin (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity was carried out in Dahu Village, Pandeglang Regency, with the main objective of introducing and implementing biopore infiltration hole technology as a simple and environmentally friendly solution to address waterlogging and organic waste management. Biopores are small-diameter vertical holes dug into the ground and then filled with organic waste, such as dry leaves, vegetable scraps, or food scraps. This organic waste will naturally decompose through a decomposition process, producing compost that is useful for fertilizing the soil. Furthermore, the presence of biopore holes can improve the groundwater absorption capacity, thereby reducing the risk of waterlogging and minor flooding around residential areas. During the implementation, we as students not only provided theoretical explanations through socialization sessions but also actively participated directly in the field. Together with residents, we practiced making biopore holes, starting from the stages of preparing tools and materials, the process of drilling the soil, and filling the holes with organic waste. This practical activity was designed to help the community understand the steps for making biopores independently and utilizing them sustainably. The results of the activity showed an increase in community understanding and awareness of the importance of easy, affordable, and beneficial waste management. The community is beginning to realize that waste processing does not always require large costs or complicated technology. Biopore holes have been proven effective in accelerating rainwater absorption, reducing household waste volume, and improving soil fertility. Beyond the environmental impact, this activity also strengthens relationships between students and villagers through the collaboration established during the biopore construction process. Thus, this program is expected to be the first step towards a cleaner, healthier, and more sustainable village.